SPECTRUM OF OCULAR MANIFESTATIONS OF RHEUMATIC AUTOIMMUNE DISEASES: A TERTIARY CARE EXPERIENCE IN PAKISTAN - Din, Zia; Khan, Asadullah; Haroon, Muhammad; Faiq, Muhammad; Rabbani, Salma; Lashari, Naveed Aslam (Journal of Ayub Medical College Abbottabad, 2021)
Background: Eye involvement is a common and potentially devastating complication of various immune related rheumatic diseases. We aimed to determine the spectrum, associations and the impact of ocular manifestations among well characterised autoimmune rheumatic disease patients presenting to ophthalmology and rheumatology clinics in a tertiary care hospital in Lahore, Pakistan. Methods: Descriptive cross-sectional study performed in Rheumatology department of Fatima memorial hospital. Only those rheumatic disease patients were included who have been attending ophthalmology department for their ophthalmic conditions. The patients with ophthalmic symptoms who have not attended an ophthalmologist were not included in this study. Proforma was designed and the studied parameters were recorded prospectively from patient's interview and also by reviewing patient's medical and ophthalmologic medical records. Parameters assessed were demographics, symptoms and the diagnosis of eye disease, unilateral or bilateral presentation, duration of eye symptoms along with the duration of the primary rheumatologic disease, and the complications of the eye disease whether due to the eye diagnosis or its treatment. Results: Eighty-three consecutive patients with mean age 33±11 years, 67.5% being female were recruited. Spondyloarthritis (SpA) comprised 38.6% (n=32) of patients followed by 21.7% (n=18) of Behcet's disease. Majority of patients (68.7%) had bilateral eye symptoms. In our cohort, 70% (n=58) of the patients had uveitis and almost all of these patients had either SpA or Behcet's disease as their primary rheumatologic diagnosis. Scleritis in 15.7% (n=13) patients followed by retinal vasculitis in 9.6% (n=8) patients, while glaucoma and keratopathy were present in 2.4% (n=2) patients each comprised other manifestations. Reassuringly our uveitis patients had no long-term eye related complications either due to the disease or its treatment. Conclusion: Uveitis represented the most common ophthalmologic manifestation associated with underlying rheumatologic diseases in our cohort, and it was associated with underlying Behcet's disease and SpA. Uveitis associated with connective tissue diseases has good prognosis with low-risk of significant long-term complications. Moreover, uveitis associated with SpA was noted to present much earlier in its disease course.